Functional connectivity between the caudate and medial prefrontal cortex reflects individual honesty variations in adults and children - Lijun Yin; Shuo Zhong; Xiaoli Guo; Zhihao Li (NeuroImage, 2021)
Deception emerges in early childhood and prevails in adults. Activation patterns in previous adults’ task-state functional magnetic resonance imaging (fMRI), though sensitive to state honesty on a specific decision, are less reliable reflecting trait honesty. Besides of state honesty, most previous neuroimaging studies about dishonesty suffer the generalization problem due to the major focus on adults with children unexplored. To investigate honesty associated functional brain networks variations, 98 healthy adults (Age: 18–28 y.o.; 49 males and 49 females) were invited to participate in a resting-state functional magnetic resonance imaging (rfMRI) study (Study 1). We investigated how functional connections between the caudate and the medial prefrontal cortex (mPFC) change among adults who differ in self-reported trait honesty. Results showed that adults with higher trait honesty have increased functional connectivity from the caudate to the mPFC, which is identified as an honesty-related hub region in global brain connectivity analysis and connects more tightly to a wide range of brain regions including the amygdala. Study 2 compared functional connectivity between children with high vs. low lying frequencies (Age: 6–16 y.o.; 61 males and 39 females) based on a publicly accessible database of rfMRI. Consistent with findings in adults, increased functional connectivity from the caudate to the mPFC was found in less frequently lying children. Despite different honesty indicators of self-reported honesty trait in adults and parent-reported lying patterns in children, consistent findings have been noted in the two samples with regards to functional connectivity variations between reward-related and self-related brain regions. These findings suggest functional connectivity alterations between the caudate and the mPFC contribute to honesty variations in both adults and children.